Immunoliposomes doubly targeted to transferrin receptor and to -synuclein - Joana A. Loureiro (2015)
Aim: The present study was designed to test the cellular uptake of PEGylated liposomes targeted to transferrin receptor and to alpha-synuclein by a cell model of the blood-brain barrier (BBB). Materials & methods: PEGylated immunoliposomes were prepared with anti-transferrin receptor OX26 and anti-alpha-synuclein LB509 antibodies to overcome the BBB in Parkinson's disease. Results: The doubly targeted immunoliposomes bind to transferrin receptor and to alpha-synuclein protein, as assessed by ELISA assays. We establish that 40% of an encapsulated tested drug (epigallocatechin-3-gallate) is released in a time frame of 44 h, which is reasonable for sustained release. The cellular uptake of doubly targeted immunoliposomes in cultured brain endothelial cells hCMEC/D3 was two-times more efficient than that of PEGylated liposomes. Conclusion: Immunoliposomes targeted to BBB receptors and to alpha-synuclein could potentially enable the transport of drugs across the BBB and reach one of the drug targets in Parkinson's disease. The blood-brain barrier (BBB) prevents the distribution of drugs into the brain, making the development of new treatments for brain disorders such as Parkinson's disease difficult. This is due to the presence of tight cell-cell junctions within the brain capillary endothelium. Nanocarriers that transport drugs across the BBB enable noninvasive modes of drug delivery (e.g., oral, systemic routes) to the brain. In the present study, we developed vesicles targeted with antibodies to BBB receptors and to a biological target of Parkinson's disease. This technology, known as Trojan horse technology, uses endogenous molecules that are able to cross the BBB through receptors present in the brain capillary endothelium.